I think it is 5/6 because you would have to choose a small amount
Answer:
2.456 x 10^11
Step-by-step explanation:
Move the decimal so there is one non-zero digit to the left of the decimal point. The number of decimal places you move will be the exponent on the 10
. If the decimal is being moved to the right, the exponent will be negative. If the decimal is being moved to the left, the exponent will be positive.
The Answer is = 8x^4
Hope this helps! :)
Answer:
100 psia
Step-by-step explanation:
Applying,
Pressure law,
P/T = P'/T'................. Equation 1
Where P = initial pressure, P' = Final pressure, T = initial temperature, P' = Final temperature.
make P' the subject of the equation
P' = PT'/T............ Equation 2
From the question,
Given: P = 50 psia, T = 300°R = (300×5/9)K = 166.66 K, T' = 600°R = (600×5/9)K = 333.33 K
Substitute these values into equation 2
P' = (50×333.33)/166.66
P' ≈ 100 psia
P ≈ 100 psia
Answer:
f(n)=f(n-1)+f(n-2)
f(1)=1x
f(2)=1x
Step-by-step explanation:
This is the fibonacci sequence with each term times x.
Notice, you are adding the previous two terms to get the third term per consecutive triples of the sequence.
That is:
1x+1x=2x
1x+2x=3x
2x+3x=5x
3x+5x=8x
So since we need the two terms before the third per each consecutive triple in the sequence, our recursive definition must include two terms of the sequence. People normally go with the first two.
f(1)=1x since first term of f is 1x
f(2)=1x since second term of f is 1x
Yes, I'm naming the sequence f.
So I said a third term in a consecutive triple of the sequence is equal to the sum of it's two prior terms. Example, f(3)=f(2)+f(1) and f(4)=f(3)+f(2) and so on...
Note, the term before the nth term is the (n-1)th term and the term before the (n-1)th term is the (n-2)th term. Just like before the 15th term you have the (15-1)th term and before that one you have the (15-2)th term. That example simplified means before the 15th term you have the 14th and then the 13th.
So in general f(n)=f(n-1)+f(n-2).
So the full recursive definition is:
f(n)=f(n-1)+f(n-2)
f(1)=1x
f(2)=1x